ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KAKI LIMA SETELAH DI RELOKASI DI TAMAN AKCAYA - B21112024, NERI (Jurnal Curvanomic, 2017)
Revenue traders can be affected by various factors. This research was conducted to find out the extent of the influence factor of capital, long hours of work and effort towards the income of street vendors in the Park Akcaya after the relocation. The source of the data in this study there are two kinds, namely primary and secondary data is data, and some of the resultof the research literature. Whereas technical analysis using multiple linear regression test, test, test the classical assumption koefesien determination, t-test and F-test statistics, statistics. From the results of research that has been done, it is noted that: (1) Variable capital effect not significant income Sellers indicated by the value of the koefesien regression of-0.072 where significant grades of 0.064 greater than 0.05. (2) old business influential Variables significantly to revenues of street vendors is indicated by the value of the koefesien regression of significant value where 0.374 of 0.019 smaller than 0.05. (3) the variable work hours effect significantly to revenues of street vendors is indicated by the value of the koefesien regression of 0.364 where the significant value of 0.023 smaller than 0.05. Keywords: income, capital, long hours of work and effort